Study of Lecturer Performance at Private University Case Study in Bandung and Cimahi, West Java - Nano Sukmana (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study is to describe the increase in understanding of the fraction The important role of private universities is increasingly felt in the midst of the limited number of state universities. Private universities are proven to be able to accommodate 300% more students than state universities. Thus, so that human resources are qualified. The quality of private higher education institutions needs to have a serious concern from the leader. This research is a quantitative descriptive study that wants to capture the performance of private universities based on the quality and performance of lecturers, management performance and learning outcomes. The study was conducted at 4 (four) private universities in Bandung and Cimahi, West Java Province which had educational characteristics. The used data are obtained from documents and are strengthened by data from surveys and interviews for each variable of university performance. All data were quantified using a Likert scale and categorized into four qualifications namely very good, good, moderate, and low, and analyzed the correlation with student learning outcomes. The results of the study indicate that the performance components of private universities, in general, need to be improved because they are still in moderate qualifications. The management component has the highest score, followed by sequential components of lecturer quality and lecturer performance. In general, student learning outcomes are also in the moderate category. The three components analyzed have a very strong influence on student learning outcomes.